DEVELOPMENT OF MOSQUE ORGANIZATIONS AS LEARNING ORGANIZATIONS IN THE PERSPECTIVE OF MARQUARDT'S THEORY - Nurzaelani, Mohammad Muhyidin; Wiratomo, Yogi; Japar, Muhammad; Herdiati, Dian (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2025)
Currently, there is an interesting phenomenon related to the development and enthusiasm for prospering mosques in Indonesia. Not only related to the development of their numbers, the development of their building designs, but also related to the development of their organizations and management. The current trend in mosque management shows more professional mosque management, mosques are no longer just places of prayer, but many mosque organizations are trying to restore the function of mosques as in the time of the Prophet Muhammad SAW, as a place of worship that can also play a role and function as a place of education and social community. This research was conducted using a qualitative research method with a literature review approach or with a library research type. This research utilizes literature (library) in the form of journals, proceedings, and books. The main focus of this research is to analyze and describe how to develop mosque management into a learning organization from the perspective of Marquardt's theory, namely a systems learning organization model that includes learning, organization, humans, knowledge, and technology. From various information related to the profile, programs, and activities of mosques in Indonesia, it can be seen that many mosques have become learning organizations. Marquardt's theory on the learning organization system model can be a framework for mosque organizations in developing mosques as learning organizations whose members have a strong and collective desire to learn continuously to improve themselves and their organization for mutual success.